Effect of feasibility analysis of business development of badman coffee shop and waffle - Muhammad Prasta Lazuardie (Har Press Indonesia, 2023)
Badman Coffee & Waffle Coffee Shop is a shop that runs its business, especially in the field of coffee, as one that provides coffee drinks with characteristics that are different from other shops. This research is based on the fact that the Badman and Waffle coffee shop has been running its business well so far, but the problem with the current location is that it is not strategic because the location is not spacious enough to only accommodate four table stands while there are quite a lot of visitors who come to the location. The purpose of this study is to analyze the feasibility of the Badman coffee shop business which includes marketing aspects, human resource aspects, operational management aspects, financial aspects, and legal aspects. This study uses descriptive analysis by collecting data through observation, interviews with owners, managers and visitors and distributing questionnaires to customers of Badman and Waffle Coffee shops to obtain secondary data relating to the purpose of analyzing the feasibility of developing the Badman and Waffle coffee shop business with SWOT analysis. The results of the study concluded that Badman and Waffle coffee shop is feasible for business development to a wider and strategic location.